Ink-jet printing technology enables self-aligned mould patterning for electroplating in a single step. (June 2015) - Meissner, M V; Spengler, N; Mager, D; Wang, N; Kiss, S Z; Höfflin, J; While, P T; Korvink, J G
Abstract We present a new self-aligned, mask-free micro-fabrication method with which to form thick-layered conductive metal micro-structures inside electroplating moulds. Seed layer patterning for electroplating was performed by ink-jet printing using a silver nano-particle ink deposited on SU-8 or Ordyl SY permanent resist. The silver ink contact angle on SU-8 was adjusted by oxygen plasma followed by a hard bake. Besides functioning as a seed layer, the printed structures further served as a shadow mask during patterning of electroplating moulds into negative photoresist. The printed silver tracks remained in strong adhesion to the substrate when exposed to the acidic chemistry of the electroplating bath. To demonstrate the process, we manufactured rectangular, low-resistivity planar micro-coils for use in magnetic resonance microscopy. MRI images of a spring onion with an in-plane resolution down to 10 µm × 10 µm were acquired using a micro-coil on an 11.7 T MRI scanner.